Introduction to computer-intensive methods of data analysis in biology - Roff, Derek A., 1949- (Cambridge University Press, 2006)
Roff offers an introduction to modern computational tools such as Maximum Likelihood, Monte Carlo and Bayesian methods for the analysis of biological data using S-PLUS, a statistical software package. This book is useful for graduate level students and researchers across the biological sciences.